SOME PROBLEMS OF STUDENT INDIVIDUAL WORK ORGANIZATION AT TECHNICAL UNIVERSITY - I. O. LEUSHIN; I. V. LEUSHINA (Высшее образование в России)
The paper addresses some problems of students’ individual work organization at technical university. Among them the authors mark out the discrepancy between the traditional interpretation of a term “student individual work” by the academic community and its treatment by the Ministry of Education and Science of the Russian Federation, the low students’ motivation to individual work, the lack of a clear selection algorithm of certain forms and methods of individual work that have already proved their efficiency and understandable for lecturers, university teachers’ disregard to different levels of students’ preparedness to self- dependent work. The authors propose a variable approach to formation of study time balance ensuring an optimal ratio of face-to-face learning and students’ individual work.